Pengaruh Work Life Balance dan Lingkungan Kerja Non Fisik terhadap Kinerja Pegawai Pada Badan Kepegawaian Daerah Provinsi Sumatera Barat yang Dimediasi Kepuasan - Dwitama, Febiolin; Ariyanto, Edi (Jurnal Informatika Ekonomi Bisnis, 2024)
Life balance in the implementation of work is an inseparable part of achieving employee job satisfaction, while job satisfaction is one of the most important parts of employee performance so that company goals are achieved effectively and efficiently. The aim of this research is to analyze the influence of work life balance and non-physical work environment on the performance of employees of the Regional Civil Service Agency of West Sumatra Province which is mediated by job satisfaction. The total population in this study was 73 people who were the samples in this study using the census or saturated sample method. Data was collected through distributing questionnaires with a Likert scale model and then testing the validity and reliability of the questionnaire. The data analysis technique used is the Smart PLS method. The results of this research are that work life balance has a positive and significant influence on employee performance at the Regional Civil Service Agency of West Sumatra Province; The non-physical work environment has a positive and significant influence on employee performance at the West Sumatra Province Regional Civil Service Agency. Work life balance has a positive and significant influence on job satisfaction at the Regional Civil Service Agency of West Sumatra Province. The non-physical work environment has a positive and significant influence on job satisfaction at the Regional Civil Service Agency of West Sumatra Province. Job satisfaction has a positive and significant influence on employee performance at the Regional Civil Service Agency of West Sumatra Province. Work life balance can be mediated by job satisfaction on employee performance at the Regional Civil Service Agency of West Sumatra Province. The non-physical work environment can be mediated by job satisfaction on employee performance at the Regional Civil Service Agency of West Sumatra Province.